Mild cold‐stress depresses immune responses: Implications for cancer models involving laboratory mice. (25th July 2014) - Messmer, Michelle N.; Kokolus, Kathleen M.; Eng, Jason W.‐L.; Abrams, Scott I.; Repasky, Elizabeth A.
<x xml:space="preserve">Abstract</x> Physiologically accurate mouse models of cancer are critical in the pre‐clinical development of novel cancer therapies. However, current standardized animal‐housing temperatures elicit chronic cold‐associated stress in mice, which is further increased in the presence of tumor. This cold‐stress significantly impacts experimental outcomes. Data from our lab and others suggest standard housing fundamentally alters murine physiology, and this can produce altered immune baselines in tumor and other disease models. Researchers may thus underestimate the efficacy of therapies that are benefitted by immune responses. A potential mediator, norepinephrine, also underlies stress pathways common in mice and humans. Therefore, research into mechanisms connecting cold‐stress and norepinephrine signaling with immune depression in mice could highlight new combination therapies for humans to simultaneously target stress while stimulating anti‐tumor immunity.